Projected Humidification Expands the Sustainable Grazing Areas in the Drylands of the Qinghai–Xizang Plateau - Tong Lu; Changjia Li; Shuai Wang; Wenxin Zhou; Yazhe Li; Zhenhua Mao; Qiang Tang; Jianbo Liu; Jiren Xu (Ecosystem Health and Sustainability)
The drylands on the Qinghai–Xizang Plateau are extremely sensitive to climate change and grazing activities. However, there is a lack of quantitative study of the combined effects of aridity and grazing pressure, which are vital in determining the sustainable grazing areas. In this study, a 2-dimensional threshold model was employed to assess the maximum allowable grazing pressure and determine the sustainable grazing areas under both historical conditions and projected climate change scenarios up to 2100. Results showed that 62.2% of the drylands under historical condition were unsuitable for grazing and 6.7% exceeded the ecological threshold, while 31.1% fell within the areas with sustainable grazing. Model projections indicate a trend toward humidification across the drylands under the climate change scenarios of RCP 4.5 and RCP 8.5. This process is expected to partially alleviate the negative impact of grazing, leading to an expansion of sustainable grazing areas to approximately 41.0% by 2100. These findings provide valuable insights for optimizing grazing strategies in the drylands of the Qinghai–Xizang Plateau in the future. The drylands on the Qinghai–Xizang Plateau are extremely sensitive to climate change and grazing activities. However, there is a lack of quantitative study of the combined effects of aridity and grazing pressure, which are vital in determining the sustainable grazing areas. In this study, a 2-dimensional threshold model was employed to assess the maximum allowable grazing pressure and determine the sustainable grazing areas under both historical conditions and projected climate change scenarios up to 2100. Results showed that 62.2% of the drylands under historical condition were unsuitable for grazing and 6.7% exceeded the ecological threshold, while 31.1% fell within the areas with sustainable grazing. Model projections indicate a trend toward humidification across the drylands under the climate change scenarios of RCP 4.5 and RCP 8.5. This process is expected to partially alleviate the negative impact of grazing, leading to an expansion of sustainable grazing areas to approximately 41.0% by 2100. These findings provide valuable insights for optimizing grazing strategies in the drylands of the Qinghai–Xizang Plateau in the future.